Analyzing Figures of Speech in Sherlock Holmes’ Utterances in Sherlock (Season 1, Episode 1: "A Study in Pink") - Mochamad Afandi (JLER (Journal of Language Education Research), 2026)
This study explores the use of figures of speech in Sherlock Holmes’s utterances in Sherlock (Season 1, Episode 1: A Study in Pink). The research highlights the importance of analyzing figurative language in television dialogue as a medium to enrich character portrayal and narrative depth. Using Leech's (1969) theoretical framework, this study identifies and categorizes 64 instances of figures of speech, including irony, metaphor, hyperbole, and litotes. Data collection involved transcript analysis and time-coding of Sherlock’s dialogue. Findings reveal that irony is the most frequently used figure of speech, followed by metaphor and hyperbole. These rhetorical devices serve to emphasize Sherlock's intellectual sharpness and dramatic communication style, engaging the audience while subtly conveying layered meanings. This research underscores the value of figurative language in enhancing the storytelling experience and character complexity in television series.